2018
DOI: 10.1177/2050312118767234
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective review of treatment patterns of antiemetic agents for chemotherapy-induced nausea and vomiting

Abstract: Objectives:To evaluate the treatment pattern of antiemetic agents used for chemotherapy-induced nausea and vomiting in a tertiary hospital in Saudi Arabia.Methods:Over a period of 7 weeks, all new chemotherapy order sheets were collected and evaluated for chemotherapy-induced nausea and vomiting management. We compared each antiemetic regimen used for chemotherapy-induced nausea and vomiting prophylaxis with three international antiemetic guidelines by the following organizations: the Multinational Association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
2
4
1
2
Order By: Relevance
“…Aprepitant prescribing has been observed to be low in studies from Indian and Saudi Arabian tertiary centers, probably due to its high cost. [ 18 19 ] Olanzapine has also been reported to be infrequently prescribed. [ 18 ] From a general perspective, the cost of olanzapine at the study site was relatively high and could have contributed to its low prescribing rate.…”
Section: Discussionmentioning
confidence: 99%
“…Aprepitant prescribing has been observed to be low in studies from Indian and Saudi Arabian tertiary centers, probably due to its high cost. [ 18 19 ] Olanzapine has also been reported to be infrequently prescribed. [ 18 ] From a general perspective, the cost of olanzapine at the study site was relatively high and could have contributed to its low prescribing rate.…”
Section: Discussionmentioning
confidence: 99%
“…Neither studies reported the impact of CINV on patients quality of life. 22,23 Arabic is the sixth most frequently used language and is estimated to be the native tongue of 420 million people worldwide. With the projection of a 1.8-fold increase in cancer incidence in the Arab world by 2030, 24 it is imperative to utilize self-assessment instruments such as FLIE as part of the care in patients actively receiving chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Os fatores de risco para o desenvolvimento de náusea e vômitos induzidos por quimioterapia envolvem, além do potencial emetogênico dos agentes quimioterápicos, pacientes jovens, do sexo feminino, com histórico de náusea e vômito durante gravidez. Por outro lado, distúrbios eletrolíticos e lesões estruturais no esôfago ou estômago também se relacionam com a ocorrência dessas toxicidades gastrointestinais 22 . Além desses fatores de risco, um estudo com mulheres em tratamento do câncer de mama identificou que 42% das participantes não aderiram aos protocolos antieméticos, bem como a escolaridade, o consumo de álcool e experiências anteriores com agentes quimioterápicos influenciaram nessa não adesão 23 .…”
Section: Discussionunclassified